SAT0294 ANALYSIS OF POLIAUTOIMMUNITY IN THE DIFFERENT SUBSETS OF SCLERODERMA. (June 2019) - Sánchez-Cano, Daniel; Ortego, Norberto; Callejas-Rubio, Jose Luis; Tolosa, Carles; Castillo, Alfredo Guillén del; Argüelles, Dolores Colunga; Sáez-Comet, Luis; Rubio-Rivas, Manuel; Argibay, Ana; Fonollosa-Pla, Vicent; Simeón-Aznar, Carmen Pilar; ,
Abstract : Background: Coexistence of different connective tissue diseases based on their common autoimmune base is a feasible circumstance, which is known as poliautoimmunity (PAI). Objectives: Evaluation of the occurrence of PAI in systemic sclerosis (SSc) according to subtypes in the patients included in the Spanish SSc Registry (RESCLE). Causes of death were also analyzed. Methods: A nationwide, cross-sectional study was carried out. All participating centers had obtained local ethics committee approval. Results: PAI was present in 46% out of 1911 patients, of whom, 33% had more than one association. Most of these patients were women (93%, p<0.001), with no significant differences regarding first manifestation: Raynaud's phenomenon, puffy hands, arthralgia or skin sclerosis. Isolated SSc was more frequent in all subsets (table 1 ). Sjogren's syndrome was by far the most frequent associated disorder, with a RR of 1376 (table 2 ). Causes of death (SSc-related or not) did not significantly differ whether PAI was present or not. Conclusion: A rather higher prevalence than reported was observed, although distribution of the associated disorders was similar. No remarkable differences were found regarding SSc subsets, either PAI prevalence, initial manifestations or causes of death. Disclosure of Interests: None declared